The drunken officials of Abdülhamid II: Alcohol consumption in the late ottoman bureaucracy - KIRMIZI, ABDULHAMİT (My University, 2022)
The established ideal, official and formal views have stood in the way of sufficient research on the practices of alcohol consumption in Muslim societies. This study will portray officials of a Muslim state under the rule of a caliph as breakers of alcohol regulations. The Ottoman Sultan Abdülhamid II (r. 1876-1909) is known in the literature for his piety and Islamist policies. His officials, even those closest to him, were not that religious and frequently crossed the lines drawn by their master. There is overwhelming evidence suggesting that alcohol use by state officials both outside the office and in the office was a considerable problem for higher authorities. In the Ottoman personnel registers (sicill-i aḥvāl defterleri) of the time, which also contain information on disciplinary matters, one can find many functionaries with drinking problems among the fifty-thousand registrees. The article does not touch upon the religious ban on alcohol use but its impact on disciplinary measures in modern regulations concerning the officialdom. How was suspected intoxication officially discussed? The investigation on the bureaucratic discourse on drinking is followed by an examination of the disciplinary measures. Were there any laws concerning the consumption of alcohol by state officials? What were the needed conditions to face discipline or suspension? How far were the measures enforced? How were they buzzed, journaled, or accused: by their directors, colleagues, or civils? The personnel registers enable us to investigate who was drinking when and where. Many profiles have a conservative family and education background, there are drinkers from ulama and sufi families, and with madrasa education. Lastly, the article articulates where and when the officials were drinking. Against the grain of Istanbul-centered westernisation narratives prioritising educated French-speaking Ottoman elites, this study will show drinking Muslim officials from provincial administration with no western language skills and mostly without a university-level education. None of the habitually drinking officials exposed in the article knew French; they were born, lived and worked in the provinces.

Le sultan Abdülhamid II (r. 1876-1909) est connu dans la littérature pour sa piété et sa politique islamiste. Beaucoup des fonctionnaires de l’époque, même parmi ses plus proches, n’étaient pas si religieux et dépassaient fréquemment les limites tracées par leur sultan. Les registres du personnel ottoman (sicill-i aḥvāl defterleri) contiennent des informations sur les mesures disciplinaires, et révèlent que de nombreux fonctionnaires avaient des problèmes d’alcool. Qui buvait quand et où ? Certains avaient une famille et une éducation conservatrices ; parmi les buveurs certains appartenaient à des familles d’oulémas et de soufis et avaient effectué leur éducation à la madrasa. L’article examine les mesures disciplinaires dans les réglementations modernes et les lois existantes sur la consommation d’alcool par les fonctionnaires de l’État. À contre-courant des récits sur l’occidentalisation des fonctionnaires centrés sur Istanbul et donnant la priorité aux élites ottomanes instruites, cette étude porte sur des fonctionnaires musulmans buveurs de l’administration provinciale sans aucune connaissance des langues occidentales et majoritairement sans un niveau d’éducation élevé.

يُعرف السلطانُ عبد الحميد الثاني، الذي امتدت فترة حكمه من 1876 إلى 1909، في الأدبيات بتقواه وسياسته ذات التوجه الإسلاموي، بيد أن كثيرًا من الموظفين في عهده، حتى في أوساط أقرب المقرّبين إليه، لم يكونوا شديدي التدين، وكانوا كثيرًا ما يتعدّوْن الحدودَ التي سطّرها لهم سلطانُهم. تحتوي دفاترُ سجل الأحوال على معلومات تخصّ التدابير التأديبية التي كانت تُتّخذ إزاءهم. ومن خلالها، بوسعنا أن نلاحظ أنّ العديد من الموظفين كانوا يعانون من مشاكلَ ذات صلة بالكحول. من كان يتناول المشروبات الكحولية وأين كان يتناولها ؟ كان بعض هؤلاء الشرّيبين ينحدرون من عائلات محافظة وتلقوا تعليمًا محافظًا، فمنهم من كان سليلَ أسر من العلماء والمتصوّفة ودرس في المدارس الدينية. يتطرق المقال إلى التدابير التأديبية في التنظيمات الحديثة والقوانين السارية آنذاك والمتعلقة باستهلاك موظفي الدولة الكحولَ. وعكس تيار السرديات عن "تغرّب" الموظفين العثمانيين التي تتمحور حول إسطنبول وتعطي أولوية اهتمامها للنخب العثمانية المثقفة، ستهتم هذه الدراسة بشاربي الكحول في أوساط الإدارة في أقاليم الدولة ممّن لم تكن لهم دراية باللغات الغربية ولم يكن مستوى تعليم أغلبيتهم مستوى عاليًا.
الموظّفون الثمالى في عهد عبد الحميد الثاني: استهلاك الكحول في أوساط البيروقراطية العثمانية في عصرها المتأخر
Les fonctionnaires ivres d’Abdülhamid II : la consommation d'alcool dans la bureaucratie ottomane tardive
Keywords: Sosyal ve Beşeri Bilimler; Tarih; Social Sciences and Humanities; History; Sanat ve Beşeri Bilimler (AHCI); Sosyal Bilimler (SOC); Sanat ve Beşeri Bilimler; TARİH; Arts & Humanities (AHCI); Social Sciences (SOC); ARTS & HUMANITIES; HISTORY; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities